Acute respiratory flow restriction affects average power, but not heart rate and subjective perceived exertion in healthy women - Veiga,Rousseau Silva da (2021)
ABSTRACT This study aims to verify the effect of the restriction of the ventilatory flow on HR, RPE, and power during HIT-test performed by healthy women. The participants (n=8) underwent HIT-test without and with ventilatory flow restriction. HR, power, and RPE was measured. HRpost showed no significant difference between conditions (p=0,053). The average power presented higher values in the condition without the restriction of ventilatory flow (619,51±144,33W; 565,99±108,43W; p=0,001), but without differences in the fatigue index (p=0,383). In both conditions, increases in RPE were observed during the efforts (p<0,001). It is concluded that HR and RPE did not suffer acute effects from the restriction of ventilatory flow; however, the average power is decreased during HIT-test.